The Future is Graphic: Animated notation for contemporary practice. Issue 2 (August 2020) - Hope, Cat
Abstract : A growing number of musicians are recognising the importance of re-thinking notation and its capacity to support contemporary practice. New music is increasingly more collaborative and polystylistic, engaging a greater range of sounds from both acoustic and electronic instruments. Contemporary compositional approaches combine composition, improvisation, found sounds, production and multimedia elements, but common practice music notation has not evolved to reflect these developments. While traditional notations remain the most effective way to communicate information about tempered harmony and the subdivision of metre for acoustic instruments, graphic and animated notations may provide an opportunity for the representation and communication of electronic music. If there is a future for notating electronic music, the micro-tonality, interactivity, non-linear structures, improvisation, aleatoricism and lack of conventional rhythmic structures that are features of it will not be facilitated by common practice notation. This article proposes that graphic and animated notations do have this capacity to serve electronic music, and music that combines electronic and acoustic instruments, as they enable increased input from performers from any musical style, reflect the collaborative practices that are a signpost of current music practice. This article examines some of the ways digitally rendered graphic and animated notations can represent contemporary electronic music-making and foster collaboration between musicians and composers of different musical genres, integrating electronic and acoustic practices.